2022
DOI: 10.3389/fphys.2022.845156
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for SARS-CoV-2/COVID-19 on the Female Reproductive System?

Abstract: Coronavirus disease (COVID-19) has emerged as a very serious pandemic caused by the rapidly evolving transmission of the coronavirus SARS-CoV-2. Since its outbreak in 2020, the SARS CoV-2 has represented an important challenge for the physicians due to its well known respiratory sequelae. To date, the role of SARS-CoV-2 infection on organs and systems other than lungs and respiratory tract remains less clear. In particular, it remains to be investigated whether the reproductive system can be affected by the SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
1
5
0
1
Order By: Relevance
“…In conclusion, the human endometrium expresses ACE1, ACE2, and TMPRSS2 transcripts and proteins. Similar findings have been reported in recent studies [35] , [36] , [37] . The commonly used human receptive endometrial Ishikawa and RL95–2 cells both express ACE1, ACE2, and TMPRSS2 transcripts and proteins making them suitable for in vitro studies on endometrial receptivity and embryo implantation.…”
Section: Discussionsupporting
confidence: 93%
“…In conclusion, the human endometrium expresses ACE1, ACE2, and TMPRSS2 transcripts and proteins. Similar findings have been reported in recent studies [35] , [36] , [37] . The commonly used human receptive endometrial Ishikawa and RL95–2 cells both express ACE1, ACE2, and TMPRSS2 transcripts and proteins making them suitable for in vitro studies on endometrial receptivity and embryo implantation.…”
Section: Discussionsupporting
confidence: 93%
“…Ang (I-VII) is an essential stimulant for ovarian follicle development, maturation, and ovulation. Furthermore, the human endometrium expresses Ang (I-VII), mainly during the post-ovulatory phase [ 186 ]. Clarifying the effects of SARS-CoV-2 infection on human reproduction would thus give recommendations for women of reproductive age and provide a theoretical basis for the IVF and embryo transfer procedure.…”
Section: Sars-cov-2 and Reproductive Systemmentioning
confidence: 99%
“…Even though the newborn is not an organ of the mother, the newborn and the mother are an integral unit [ 187 ]. It has been reported that many factors contribute to ovary dysfunction during and after recovery from COVID-19 (immediate virus offensive, extreme immune response, and hypothalamus–pituitary–ovary axis dysfunction) [ 186 , 188 ]. Dysregulation of the adrenal gland and spermatogenesis in COVID-19 male patients have also been observed [ 179 , 185 ].…”
Section: Sars-cov-2 and Reproductive Systemmentioning
confidence: 99%
“…У жіночих репродуктивних органах (яєчники, матка, піхва та плацента) було виявлено різний рівень експресії ACE2 і TMPRSS2. Крім того, ACE2 рясно експресується в яєчниках і ооцитах, особливо під час секреторної фази менструального циклу порівняно з проліферативною фазою [5,20]. Цілком можливо, що SARS-CoV-2 може націлитися на яєчники та ооцити, викликавши пряме ураження.…”
Section: результати обговоренняunclassified